Novel automated antifungal susceptibility testing system for yeasts based on dual-detection algorithm of turbidimetry and colorimetry - Shen, Tingting; Liu, Piao; Chen, Dongmiao; Liu, Duoduo; Fang, Juan; Wang, Qian; Xu, Yinjuan; Tan, Chunjuan; Wang, Congrong (Journal of medical microbiology, 2024)
Introduction. The increasing prevalence and growing resistance of fungi present a significant peril to public health. There are only four classes of antifungal medicines available today, and few candidates are in clinical trials. Hypothesis/Gap Statement. Rapid and sensitive diagnostic techniques are lacking for most fungal pathogens, and those that do exist are expensive or hard to obtain. Aim. This study aimed to evaluate the feasibility of a novel automated antifungal susceptibility testing system, Fungus AST, in comparison to the broth microdilution method (BMD) recommended by the Clinical and Laboratory Standards Institute (CLSI). Methodology. A total of 101 clinical Candida spp. isolates were collected from the Zengcheng Branch of Nanfang Hospital and subjected to antifungal susceptibility testing. Antifungal susceptibility was assessed using the Fungus AST method and the BMD. Results. In this study, we introduce a novel automated antifungal susceptibility testing system, Fungus AST, which detects the turbidity and/or colour intensity of microdilution wells using a four-wavelength detection technology in real time and is designed to match the growth characteristics of strains over time. Based on our analysis, all reportable ranges of Fungus AST were suitable for clinical fungal isolates in PR China. Within ±twofold dilutions, reproducibility was 100 %. Considering the BMD as a referenced method, ten antifungal agents (anidulafungin, caspofungin, micafungin, fluconazole, voriconazole, posaconazole, itraconazole, amphotericin B, 5-flucytosine and nystatin) showed an essential agreement of >95 %. The category agreement of five antifungal agents (anidulafungin, caspofungin, micafungin, fluconazole and voriconazole) was excellent at >90 %. One Candida albicans isolate and voriconazole showed a major error (ME) (1.7 %), and no other ME or very ME agents were found. Conclusion. Given the above, it can be argued that the utilization of Fungus AST is a discretionary automated approach. More improvements are needed in Fungus AST compared to the BMD system for a wider range of clinical isolates, including different types of fungi.